Parameter evaluation of extraction using microwave hydrodistillation ultrasonic-pretreatment on yield of black pepper oil - Renova Panjaitan; Nove Kartika Erliyanti; Sandy Buana Putra; Achmad Pemadi Wicaksono; Alza Nadilla Syahrani; Nabila Ayu Amanda (Universitas Lambung Mangkurat, 2023)
Black pepper is one of Indonesia's agricultural commodities, contributing foreign exchange to the country. However, the economic value of this commodity has decreased. It is influenced by the lack of diversified black pepper products, which of course, have a higher value than raw material marketing. One product diversification that can be developed is black pepper oil. In obtaining essential oils, appropriate methods and technology are needed so that the resulting product is of high quality and the process is carried out efficiently. The latest methods in extraction that are being developed are microwave and ultrasonic technology. Therefore, in this study, black pepper oil extraction was carried out using the microwave hydrodistillation method, whereas previously, ultrasonic pretreatment was given for the material. In this case, observations were made on the influence of extraction parameters. Based on the research, it was found that increasing the distiller size flask and ambient temperature could increase the percentage of essential oils yield. At the same time, the longer extraction time caused a decrease in yield. Decreasing the material particle size and increasing microwave power could cause an increase in yield up to a certain point. The best results in black pepper oil extraction were obtained under extraction conditions using a distiller size of 1000mL, extraction time of 60 minutes, at an ambient temperature of 30 oC, the particle size of 60 mesh, at a power of 450 W with a yield of 1.056%, with the characteristics of having a clear greenish colour and anRI of 1.480. These specifications comply with ISO 3061:2008 for essential oil from black pepper. Thus, these parameters can be considered in the black pepper oil extraction process to produce marketable products. As a suggestion for further research, modeling, and process scale-up can be developed.